PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA REMAJA DI BANJAR JELEKA DESA BATUAN KECAMATAN SUKAWATI - Sintyawati, Ni Luh Putu (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
Jele Kabanja, Batuan Village, Sukawati District In an effort to increase interest in entrepreneurship among the younger generation, there are concerns and problems faced related to knowledge and motivation for entrepreneurship. The aim of the research is: To find out whether there is a simultaneous, partial, positive and significant influence between entrepreneurial knowledge and entrepreneurial motivation on teenagers' entrepreneurial interest in Banjar Jeleka, Batuan Village, Sukawati District. The number of samples determined using the saturated sample method was 87 people. Data analysis uses classical hypothesis testing, multiple linear regression analysis, analysis of the coefficient of determination, statistical analysis of the F test (F test), and statistical analysis of the t test (t test). Results show that entrepreneurial knowledge and entrepreneurial motivation simultaneously or partially have a significant positive influence on the entrepreneurial interest of the younger generation in Banjar Jeleka, Batuan Village, Sukawati District